Od repliky k citátu: jazykové prostředky a textová strategie ve sportovní žurnalistice - Rechzieglová, Adela (Stylistyka, 2000)
We examined some stylistic procedures in the sport-news in a newspaper, with special attention for the quotations from the original interview. We have found out that in the reporting clauses (or in the sentences immediately preceding or following a quotation) verbs are used which are marked by semantic characterization others than:s/he said etc. Following the grammatical rules most ofthose verbs should not be used in this function, but, surprisingly, they are. We also looked at the semantic relationships linking the quotation and the reporting speech and stated that in contrast to the expectation of an easy and simple style, this is often rather complex. A certain incoherence ofthe textual components in the sport-news makes it attractive for the reader by giving him the feeling ofreally being “there”, in the dazzling rapid world of the sport.